INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DASAR NEGERI 097523 PERUMNAS BATU VI KECAMATAN SIANTAR KABUPATEN SIMALUNGUN - Khairuddin Ahmad Hidayah Harahap, Wahyudin Nur Nasution, Mardianto (Pascasarjana UIN Sumatera Utara, 2018)
This study aims to find out what learning innovations conducted, furthermore, how the impact of learninginnovation, and want to know the factors supporting and inhibiting the implementation of learning innovationconducted by the State Elementary School 097523 Perumnas Batu VI Siantar District Simalungun.This research uses qualitative approach. The result of the research shows that the learning innovation isemphasized on: First, the submission of Islamic Religion Education materials is applied four learninginnovations namely contextual Teaching and Learning (CTL) strategy, power point media, mobile mediaand religious practice competition. Second, the Impact of Innovation Implementation Learning is seen inthe following two things: a) That students become trained to relate between the lessons learned and whatis happening in the environment at that time, b). Results on changing attitudes of students who are gettingbetter. Third, Supporting Factors and Factors inhibiting the implementation of Learning Innovation in theSubject of Islamic Religious Education: 1) the supporting factors of PAI learning innovation are as follows:a). The ability of teachers. b). Students ‘ability. c). Supporting facilities and infrastructure. 2). Inhibitingfactors in Learning Innovation Implementation include the following: a) .The limitations of teachers. b).Insufficient infrastructure and facilities. c). Psychological abilities and psychological psyche.Penelitian ini bertujuan ingin mengetahui apa saja inovasi pembelajaran yang dilakukan, selanjutnya bagaimanadampak dilaksanakanya inovasi pembelajaran, serta ingin mengetahui faktor-faktor pendukung dan penghambatpelaksanaan inovasi pembelajaran yang dilakukan oleh SD Negeri 097523 Perumnas Batu VI KecamatanSiantar Kabupaten Simalungun.Penelitian ini menggunakan pendekatan kualitatif. Hasil penelitian menunjukanbahwa inovasi pembelajaran yang dilakukan menekankan pada:Pertama, Penyampaian materi PendidikanAgama Islam yang diberikan menerapkan empat Inovasi pembelajaran yakni strategicontextual Teachingand Learning (CTL), mediapower point, media handphone serta perlombaan praktek ibadah. Kedua,Dampak Pelaksanaan Inovasi Pembelajaran terlihat pada dua hal berikut ini: a) siswa menjadi terlatihmengaitkan antara pelajaran yang diperoleh dengan apa yang terjadi di lingkungan saat itu, b). Perubahansikap siswa yang semakin membaik.Ketiga, Faktor Pendukung dan Faktor Penghambat pelaksanaan InovasiPembelajaran pada Mata Pelajaran Pendidikan Agama Islam: 1) faktor pendukung inovasi pembelajaranPAI adalah sebagai berikut ini: a). Kemampuan guru. b).Kemampuan siswa. c). Sarana dan prasarana.2). Faktor penghambat dalam Pelaksanaan Inovasi Pembelajaran antara lain adalah sebagai berikut:a).Keterbatasan guru. b).Sarana dan prasarana yang kurang memadaii. c).Kemampuan dan jiwa psikologissiswa yang beragam.Kata Kunci: Inovasi Pembelajaran, Pendidikan Agama Islam